ANALISIS PENERAPAN PENDEKATAN SAINTIFIK DALAM KURIKULUM 2013 DI KELAS V SD NEGERI 13 PEKANBARU - Neni Hermita; Guslinda Guslinda; Meri Muharmiati (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2020)
This study aims to describe the application of the scientific approach in the curriculum 2013 in class VB Public Elementary School 13 of Pekanbaru. This research is a descriptive qualitative study. The subjects in this study were teachers of class VB Public Elementary School 13 of Pekanbaru. Data collection techniques used in this study include: observation, interviews and documentation. The results of the study show that the teacher has carried out learning activities by applying the scientific approach. Activities carried out in learning include observing activities that have been carried out well by the teacher in learning 1 through learning 6, which is giving students the opportunity to observe pictures and reading texts. The questioning activity was not carried out properly, it did not appear that students asked questions in learning 1 to learning 6 only to the extent that the teacher asked the students. The activity of trying to do it is quite good in learning activities only visible in learning 2, learning 3 and learning 6 such as making story drawings, discussing in groups and making creations from playdough. Reasoning has been done well in learning 1 to learning 6, activities are carried out with the teacher giving independent assignments to students to make assignments in the student book. Communicating activities have been carried out well in learning 1 to learning 6 in the form of communicating orally and in writing in the form of teachers delivering material and question and answer activities and writing in the form of students making independent assignments. So, it can be concluded that the teacher of class VB Public Elementary School 13 of Pekanbaru has carried out learning by applying the scientific approach but has not been implemented optimally.